Reactionary dentinogenesis after applying restorative materials and bioactive dentin matrix molecules as liners in deep cavities prepared in nonhuman primate teeth - Duque, C.; Hebling, J.; Smith, A. J.; Giro, EMA; Oliveira, M. F.; Costa, CAD (Blackwell Publishing, 2006)
Objective: the aim of this in vivo study was to evaluate the response of the pulp-dentin complex following application of resin-modified glass-ionomer cement, calcium hydroxide hard-setting cement and EDTA-soluble preparation of dentine matrix proteins (ESDP) in deep cavities prepared in non-human primate teeth. Methods: Eighteen deep Class V buccal cavities were prepared in premolars of four capuccin monkeys. In Groups 1 and 2, the cavity floor was lined with ESDP or a resin-modified glass-ionomer cement (Vitrebond - 3M ESPE), respectively. In Group 3 (control), the cavity was lined with a hard setting calcium hydroxide cement (Dycal - Dentsply). The cavities were subsequently filled with amalgam. After 6 months, the animals were sacrificed and the teeth were prepared for microscopic assessment. Six-micron thick serial sections were stained with H/E, Masson's trichrome and Brown & Brenn techniques. Results: No inflammatory pulpal response was observed for all experimental and control Groups. However, the amount of reactionary dentin deposition differed between groups in the rank order ESDP (Group 1) > calcium hydroxide (Group 3) > resin-modified glass-ionomer (Group 2). These differences were statistically significant. Conclusions: All materials were biocompatible when applied in deep cavities. ESDP stimulated higher deposition of reactionary dentin matrix than Vitrebond and Dycal.
Keywords: pulp; dentine; bioactive molecules; dental materials; liners; dental cavities